Disharmoni Keluarga: Tren Cerai Gugat di Indonesia - Dwi Arini Zubaidah (Institut Agama Islam Tribakti Kediri, 2020)
A marriage is aimed at forming a sakinah, mawaddah and rahmah family. In wading the household ark, an issue is often a source of divorce. Today, there is a trend of divorce on the part of the wife (divorce). This article is intended to answer the increasing divorce factor and re-understanding harmonious family coaching by using the study of maqasyid ash-sharia. This article uses library research and is a descriptive analysis using the Islamic legal philosophy of maqasyid asy-syariah Jasir ‘Audah. There are three main factors that cause the adoption of divorce continues to increase, namely: an irresponsible husband; domestic violence and harassment from third parties. Whereas the overcoming of family disharmony is re-understood with the points in the sharia maqasyid namely: the character of cognition, holiness, openness, interconnected hierarchy, multidimensionality, and intentions.